Methanol leaf extracts of Chrysophyllum albidum and Irvingia gabonensis protected against dyslipidaemia and oxidative stress induced by high-fat diet in Wistar rats - Osebhahiemen Ibukun; Ehimwenma S. Omoregie (Bulletin of the National Research Centre, 2022)
Abstract Background High-fat diet (HFD) has been linked to oxidative stress, dyslipidaemia, obesity and cardiovascular diseases. Studies have shown that medicinal plants have antioxidant properties and may have protective effects against oxidative stress and dyslipidaemia induced by high-fat diet. Chrysophyllum albidum (white star apple) and Irvingia gabonensis (African bush mango) are very useful medicinal plants common in the tropical and subtropical regions of the world. This study was aimed at investigating the protective effect of methanol leaf extracts of Chrysophyllum albidum and Irvingia gabonensis against dyslipidaemia and oxidative stress in Wistar rats promoted by the consumption of HFD as well as characterize active compounds in the extracts. Thirty-six male Wistar rats were assigned into six groups of six animals each and respective groups received normal fat diet (NFD), HFD, HFD + Chrysophyllum albidum (250 mg/kg/ 500 mg/kg), HFD + Irvingia gabonensis (250 mg/kg/ 500 mg/kg) for fifty six days. Dietary intake, body weight, lipid profile and indicators of oxidative stress were measured. Results Administration of plant extracts did not change the pattern of food intake of the animals. There was a significant inhibition (p < 0.05) of increase in the body weight of rats treated with plant extracts in comparison with those rats that consumed HFD only. There was significant increase (p ˂ 0.05) in total cholesterol, triacylglycerol, low-density lipoprotein cholesterol, very low-density lipoprotein cholesterol and malondialdehyde concentrations in rats fed with HFD only when compared with NFD control and extract treated groups. However, HFD control produced significantly lower (p < 0.05) high-density lipoprotein cholesterol, reduced glutathione and glutathione peroxidase than normal control and extract treated groups. Gas chromatography flame ionization detector analysis of these extracts revealed the abundance of kaempferol, quercetin, luteolin, myricetin and naringenin and tannic acid. Conclusions The observed antioxidant and anti-dyslipidaemic properties of leaves of Chrysophyllum albidum and Irvingia gabonensis may be attributed to the presence of flavonoids and tannic acid.